Analysis of the genetic origin of European hare (Lepus europaeus) (technical literature review) - Kusza, Szilvia (Acta Agraria Debreceniensis, 2014)
Fossil datas showed that the lagomorphs appeared in Asia during the later Eocene and leporids separated from ochotonids during the Oligocen or Upper Eocene. During the Pleistocene, climatic changes induced major shifts in species distributions, forcing them to refugia. In Europe, the continuous oscillations led to the production of greater subspecific and specific diversity in the southern peninsulas (Iberia, Italy, Balkan) which were the main refugial areas for other species as well. Evolution, phylogeny and population genetics of the Lagomorpha species are still poorly known and the taxonomic distinction is still unclear for some species. Conservation genetics is the discipline which use genetic techniques and analysis methods to preserve species and dynamics. Usually it is working together with population genetics what role is to investigate the origin, the maintenance, the organization and the causes of genetic variation between natural populations. In the present study I reviewed the results of origin and phylogenetic studies of Brown hare populations from the last decades.